Stuttering’s Effect on Job Efficacy in Five Participants: Stuttering’s Effect on Job Efficacy - Rafique, Sehar; Noreen, Hafsa; Yaqoob, Saba; Ehsan, Fazaila; Shabnum Noor, Hafiza; Zahra, Mariam (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Stuttering also known as stammering is a speech disorder, in which the flow of speech is disrupted by involuntary repetitions and prolongations. Adults who stutter suffers with many problems at workplace due to speech disfluencies. To evaluate the effect of stuttering on job efficacy. A population both male and female between the age of 30 to 40 years were selected. Data for the stuttering patients were collected from different job places of Lahore. All these stutters were given the consent form. It confirmed their willingness to participate in interview. Interview guide was designed as per the criteria of research questions. Interview guide was evaluated and reviewed by two external members. Interviews were conducted on WhatsApp audio or video call, zoom meetings and face to face, according to the availability and willingness of participants. Interviews were recorded for further analysis. Recorded interviews were transcribed which were further coded, and subthemes were extracted. On the basis of subthemes, themes of the research were decided. Results shows that only those individuals who stutter doing their own business or running their own NGO’s (Non-Governmental organizations) are satisfied with their jobs/works. Individuals doing any kind of job in a private company are not satisfied with their jobs because of stuttering. Case Summary: Stuttering has a negative impact on their job performance and employment. Stuttering made them lose their confidence in front of any stranger, senior or boss. People usually mock them because of stuttering. These issues lead them towards anxiety, complexity and frustration.